Fentanyl nasal packing for management of postoperative pain control in patients of nasal bone fracture reduction - Siddiqui, Maqsood Ahmed; Aiman Shah; Hamid Mehmood; Salman Ahmed Mangrio; Muhammad Javed khan; Syed Faraz Bukhari (Medical Journal of South Punjab, 2024)
Objective: To evaluate of effect of fentanyl nasal packing in management of postoperative pain in patients of post reduction of nasal bone fracture. Methods: This randomized controlled trial was conducted at Ghulam Muhammad Mahar Medical College/Hospital, Sukkur, Pakistan from January 2022 to December 2022. Total 60 consecutive patients aged 18–65 years with nasal bone fracture admitted for reduction of fracture were included. Patients were rated according to Numeric Rating Scale at interval of one, six, twelve and twenty-four hours postoperatively, while a blinded anesthesiology resident gathered these responses. Results: The mean postoperative NRS score at 1 hour in Control Group and Fentanyl Group was 8.23±0.72 and 6.60±1.98, respectively. The average postoperative NRS score at 6 hours in Control Group and Fentanyl Group was 5.60±0.47 and 4.46±1.25, respectively. The average postoperative NRS score at 12 hours in Control Group and Fentanyl Group was 4.00±0.94 and 3.33±0.88, respectively. The average postoperative NRS score at 24 hours in Control Group and Fentanyl Group was 3.03±0.82 and 2.40±0.62, respectively. (p<0.001). Conclusion: The study suggests that topical fentanyl administration could be an effective method for managing acute nasal pain, particularly in controlling postoperative nasal pain.